Manipulation Of Public Space Design Within Cities: Architecture as A Crime Control Theory in Response to Cases of Child Violence - Johanes Krisdianto; Miranda Rahel Gultom (Center for Scientific Publication, 2024)
Data shows that, all recorded cases of violence in Indonesia, most of the victims were children. architecture needs to respond to this phenomenon by manipulating certain spatial designs, because these cases occur in architectural spaces. This issue should ideally be considered on a city scale, seeing that the highest mobility of children is movement within the city, perhaps going to school or to the playground within the same city. To create a safe environment for children from violence that lurk on a city scale, it is necessary to manipulate the design of spaces in the city where children usually carry out their activities, thus these spaces can be called child-friendly spaces. By using the theory of architecture as a crime control, which is a prevention and protection mechanism for victims and potential victims of urbanscale violence, the spatial and formal aspects that need special attention are visibility, dimensions and shape, and accessibility.